(untitled) (Medical Forum Monthly, 2024)
Objective: To observe changes in the histology of hepatic tissue of Albino rats exposed to the oral administration of toxic doses of Imatinib and to assess the protective effect of vitamin E. Study Design: Analytical experimental randomized control study. Place and Duration of Study: This study was conducted at the Department of Anatomy, Peshawar Medical College Peshawar from February 2013 to July 2013. Materials and Methods: This study of twenty four male albino rats was conducted at PCSIR lab complex and Peshawar Medical College, Peshawar. Rats were randomly divided into three groups, one control and two experimental groups. Experimental group I were treated with the oral administration of Imatinib for two weeks and experimental group II were treated with the oral administration of same dose of Imatinib with the concomitant administration of vitamin E. Haematoxilin and Eosin used for routine examination Masson Trichrome for hepatocellular necrosis and fibrosis. Results: Scoring system was applied to evaluate the degree of toxic effect of Imatinib on the hepatic tissue of rats. The degree (no change, mild to moderate change and marked change) of hepatocelluler necrosis were observed. It is concluded that the most affected rats were those treated with Imatinib i.e. experimental I. Rats in experimental II, which received antioxidant in addition to Imatinib were least affected, thus conforming the protective role of vitamin E. Conclusion: The simultaneous use of antioxidant vitamin E with Imatinib could prevent the hepatic toxicity which includes hepatocelluler necrosis.